Leukotriene B4 levels in sputum from asthma patients. Issue 4 (26th October 2016) - Higham, Andrew; Cadden, Paul; Southworth, Thomas; Rossall, Matthew; Kolsum, Umme; Lea, Simon; Knowles, Richard; Singh, Dave
Poor asthma control is associated with increased airway neutrophils. Leukotriene B4 (LTB4) is a potent neutrophil chemoattractant. We examined the levels of LTB4 levels in the sputum of asthma patients and the relationship with disease severity. 47 asthma patients (categorised according to Global Initiative for Asthma treatment stage) and 12 healthy controls provided sputum samples that were processed first with PBS to obtain supernatants and secondly with dithiothreitol (DTT) to obtain supernatants. LTB4 levels were determined by ELISA. LTB4 levels were significantly higher in step 1 (steroid naïve) and step 3 (inhaled corticosteroid (ICS) plus long acting β-agonist) patients than step 2 patients (ICS alone) (p=0.02 and p=0.01, respectively). There was very good correlation when comparing PBS processed to DTT processed supernatants. High LTB4 levels were found in the sputum of asthmatics at step 3 despite ICS use. The levels of LTB4 are increased in the sputum of subgroups of asthma patients http://ow.ly/Xu6I303jVb5